(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the demographic data as well as clinical profile and outcome of DKA in children aged < 18 years with T1DM. Study Design: Observational / case series study Place and Duration of Study: This study was conducted at the Pediatrics unit 2 of Bahawal Victoria Hospital, Bahawalpur from January 2017 to November 2018. Materials and Methods: This study was conducted on children aged < 18 years admitting with T1DM with DKA. Demographic features, clinical presentation, laboratory findings and outcome were recorded for all patients. Results: A total of 52 children of T1DM with DKA were reported during the study period. Mean age amongst all the patients was 9.8 years. Most of the patients i.e. 66.7% cases belonged to urban areas and 59.6% cases newly diagnosed cases of T1DM. The most frequent symptoms at the time of hospitalization were polyuria 88.5% and polydipsia 82.7%. Mean time for recovery amongst all was 23.4 hours while 2 (3.8%) deaths occurred during hospital stay. The most frequent complication seen were hypokalemia 20 (38.5%) and hypernatraemia 16 (30.8%). Conclusions: Diagnosis of T1DM should be made at earliest so that DKA and its complications can be prevented in our population.